Autistic Adult Online Interoception Feasibility Pilot Program. - Graziosi, Sophia; Oliver, Emily; Arline, Victoria; Mahler, Kelly; Ratcliff, Karen; Pryor, Loree; Hilton, Claudia; Kaushik, Shashank (Occupational Therapy International, 2026)
Interoception differences are known to co‐occur with autism and result in difficulty recognizing and addressing internal signals, which can produce barriers to daily living and quality of life (QoL). Limited supportive services have addressed these needs in autistic adults, and occupational therapists are well prepared to provide interventions to address these challenges. The objectives of the study were to: (1) examine feasibility of an 8‐week online interoception program for autistic adults and (2) examine quantitative changes after participation in the program. The program was adapted from the Interoception Curriculum for 10 autistic adults. Outcome measures included standardized questionnaires for interoception, anxiety, alexithymia, QoL, and self‐designed questionnaires for program evaluations. Researchers were supported throughout the process by a paid autistic occupational therapist to guide development of the research question, methodology, and adaptation of support materials to incorporate lived experience and community engagement. Preintervention and postintervention scores were compared for interoceptive awareness, alexithymia, anxiety, and QoL, which showed insignificant improvements in all areas with a range of small to large effect sizes over the 8 weeks. Participants reported positive feelings about the program and would recommend it to others. Results support the feasibility of an online interoception program for autistic adults.